Where is the violence in identity-related violence? The generative potentiality of violence in ethno-religious conflict and mass purging in Indonesia - Geger Riyanto (Universitas Negeri Yogyakarta, 2020)
This article argues that we have to address the generative potentiality of violence in drawing a rigorous depiction of identity-related violence. Works on identity-related violence often explain the violence as culminating from the perpetrators’ sense of identity. Even though to some extent such an explanation sheds light on the perpetrators’ motivation, it is prone to reducing the actuality of violence to a mere epiphenomenon. In actual circumstances of conflict and purging, the frightening and engrossing horror of violence convincingly imposes the antagonistic discursive boundary of self and other on the involved subject’s senses. As an efficacious embodiment of identity, violence also entails the subjects perpetually performing it in a way that reinforces the facticity of the fictive categories of identity and eventually escalates the violence. This article makes its case through an examination of two incidents of massive violence in Indonesia: the 1966-69 communists purging and the 1999-2002 ethno-religious conflict in Maluku.